Pengaruh Kecerdasan Emosional, Independensi, Dan Profesionalisme Terhadap Pengambilan Keputusan Auditor Pada Kantor Akuntan Publik Padang - Netti Herawati; Agussalim M; Titi Darmi (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
ABSTRACT This study aims to determine whether the emotional intelligence, independence, and professionalism of the auditors in decision making at the Padang Public Accountant Office either partially or simultaneously. The method in this research uses multiple linear regression data analysis and determination. The results of the research show that the intelligence coefficient of intelligence is 0.379 with a significant value of 0.094, this indicates that the significant value is 0.094> alpha 0.05, so emotional intelligence has no positive effect on the auditor's decision, the regression coefficient value is -0.097 with a significant value of 0.519. , this shows that the significant value is 0.519> alpha 0.05, so the independence does not have a negative effect on auditor decision making, while the professionalism regression coefficient value is 0.526 with a significant value of 0.009, this indicates that the significant value is 0.009 <alpha 0, 05 then professionalism has a positive effect on auditor decision making. The conclusions of this investigation are emotional intelligence, independent, and auditor professionalism simultaneously have a significant effect on decision making at the Padang Public Accounting Firm either partially or simultaneously. Keywords: Emotional Intelligence, Decision Making, Independence, Professionalism.